2009
DOI: 10.1111/j.1600-0447.2009.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network connectivity as a predictor of post‐traumatic stress disorder symptom severity in acutely traumatized subjects

Abstract: These results may contribute to the development of prognostic tools to distinguish between those who will and those who will not develop PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
225
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 42 publications
24
225
0
Order By: Relevance
“…Consistent with this, a study of resting-state functional connectivity between the posterior cingulate and other brain regions in a group of acutely traumatized adults found that the degree of connectivity with bilateral anterior cingulate region is positively associated with the severity of PTSD symptoms (i.e., the most severe cases had the greatest coordinated activity between posterior and anterior cingulate) [7] .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with this, a study of resting-state functional connectivity between the posterior cingulate and other brain regions in a group of acutely traumatized adults found that the degree of connectivity with bilateral anterior cingulate region is positively associated with the severity of PTSD symptoms (i.e., the most severe cases had the greatest coordinated activity between posterior and anterior cingulate) [7] .…”
Section: Discussionmentioning
confidence: 63%
“…For example, two studies compared women with early-life trauma to healthy women [6] and examined the relationship between coordinated activity in the resting state and PTSD symptoms in an acutely traumatized sample [7] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that DMN connectivity may have potential as a predictor of PTSD symptom severity in acutely traumatised subjects (Lanius et al, 2010). In an attempt to explore the potential of the abovementioned dysconnectivity as a biological marker for BPD, it is recommended that future studies should also carry out functional connectivity analyses in the most commonly documented comorbidities of BPD, which are MDD, attention deficit hyperactivity disorder (ADHD), and PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study investigated the relationship between default mode network connectivity and the severity of PTSD symptoms in subjects who had experienced an acute traumatic event 6-12 weeks before. The results of this study suggest that the resting-state connectivity of the posterior cingulate cortex/precuneus with the perigenual ACC and right amygdala is associated with current PTSD symptoms and that the correlation with the right amygdala predicts future PTSD symptoms (Lanius et al, 2010). Another study measuring resting-state amygdala connectivity in male veterans with PTSD (n=15) and in combat controls (n=14) showed greater positive connectivity between the amygdala and the insula in patients with PTSD than in controls, reduced positive connectivity between the amygdala and the hippocampus, and a reduced anticorrelation between the amygdala and the dorsal and rostral ACC (Sripada et al, 2012).…”
Section: Traumatic Experiences Disrupt Amygdala-prefrontal Connectivitymentioning
confidence: 71%